2005
DOI: 10.1007/s10661-005-3608-y
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Large, Statewide Database to the Assessment, Stressor Diagnosis, and Restoration of Stream Fish Communities

Abstract: In this report, predictions of the species that were expected to occur at stream sites were generated and probable stressors to fish species that were predicted to occur but were absent were diagnosed. Predictions were generated based on the hierarchical screening method of Smith and Powell (1971, Am. Mus. Novit. 2458, 1-30), using fish abundance in conjunction with 25 environmental variables at 895 sites. The sites were sampled throughout Maryland and represent the entire range of environmental quality from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The MBSS data set includes over 3,000 randomly selected sites sampled during three state-wide Rounds and approximately 1,000 non-random sites and has been extensively published on using fish and benthic macroinvertebrate as response organisms (e.g. Pinder & Morgan, 1995;Morgan & Cushman, 2005;Stranko et al, 2005;Stranko et al, 2008;Kilian et al, 2010;Hildebrand et al, 2010). Despite the fact that freshwater mussels are good response organisms for understanding spatial and temporal environmental patterns (Green et al, 1985), only two publications (Mynsberge et al, 2009;Stranko et al, 2010) have included MBSS-mussel observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MBSS data set includes over 3,000 randomly selected sites sampled during three state-wide Rounds and approximately 1,000 non-random sites and has been extensively published on using fish and benthic macroinvertebrate as response organisms (e.g. Pinder & Morgan, 1995;Morgan & Cushman, 2005;Stranko et al, 2005;Stranko et al, 2008;Kilian et al, 2010;Hildebrand et al, 2010). Despite the fact that freshwater mussels are good response organisms for understanding spatial and temporal environmental patterns (Green et al, 1985), only two publications (Mynsberge et al, 2009;Stranko et al, 2010) have included MBSS-mussel observations.…”
Section: Discussionmentioning
confidence: 99%
“…The Maryland Biological Stream Survey (MBSS) is a statewide biological monitoring and assessment program administered by the Maryland Department of Natural Resources' Monitoring and Non-Tidal Assessment Division, which has incorporated freshwater mussels into standard operation procedures (Stranko et al, 2007). Objectives of the MBSS are to assess the condition of aquatic resources, identify physiochemical and anthropogenic stressors such as acidification, land alteration, and climate change, and provide an inventory of biodiversity in Maryland's streams (Klauda et al, 1998;Stranko et al, 2005). This is primarily accomplished through a probabilistic design to make unbiased estimates on the condition of the states' (1st-4th order) wadeable streams (Heimbuch et al, 1999), but has recently included other sampling designs tailored to meet resource management needs.…”
Section: Introductionmentioning
confidence: 99%
“…Also, this taxonomic level was shown to present similar responses to impairment as lower levels in Brazil (Buss & Vitorino 2010) and, due to practical reasons, family-level is recommended as a starting point for bioassessments in regions with taxonomic and resources constraints, such as Brazil (Buss et al 2015). Other studies developing predictive modelling based on environmental filters (Chessman & Royal 2004, Stranko et al 2005, Chessman 2006, Walsh et al 2010, Davies et al 2012 have found that those approaches may be applied successfully using family level.…”
Section: Development Of the Predictive Modelmentioning
confidence: 96%
“…The need to implement bioassessment programs in regions where reference sites are absent or scarce have fostered the development and testing of alternative methods (Chessman & Royal 2004, Carter & Fend 2005, Stranko et al 2005, Chessman 2006, Blocksom & Johnson 2009, Hawkins et al 2010, Birk et al 2012, Schoolmaster et al 2013, Labay et al 2015, Milošević et al 2016, Elias et al 2016. Some researchers point that an approach that does not require the use of reference sites should be explored (Olden et al 2006, Feio et al 2009, Feio & Poquet 2011, Elias et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation